2023
DOI: 10.1111/ans.18812
|View full text |Cite
|
Sign up to set email alerts
|

The association of body composition on chemotherapy toxicities in non‐metastatic colorectal cancer patients: a systematic review

Cheuk Shan Choi,
Kamol Kin,
Ke Cao
et al.

Abstract: BackgroundIn recent years, certain body composition measures, assessed by computed tomography (CT), have been found to be associated with chemotherapy toxicities. This review aims to explore available data on the relationship between skeletal muscle and adiposity, including visceral adipose tissue (VAT), subcutaneous adipose tissue (SAT), intramuscular and intermuscular adipose tissue and their association with chemotherapy toxicity in non‐metastatic colorectal cancer (CRC) patients.MethodsA systematic literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Current studies on chemotoxicity in CRC mainly focus on patient-reported outcomes (PROs) [12,14] and cancer treatment outcomes (e.g., response rates, cancer death) [20][21][22]. In previous studies comparing adverse events between PROs versus clinician-reported outcomes (e.g., grading scales, diagnostic codes, or progress notes) in lung cancer [23], and mixed cancer types [24], patients generally reported symptoms earlier and more frequently than clinicians, had a higher incidence and severity of subjective toxicities, and had poor to modest agreement with clinician-reported values [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Current studies on chemotoxicity in CRC mainly focus on patient-reported outcomes (PROs) [12,14] and cancer treatment outcomes (e.g., response rates, cancer death) [20][21][22]. In previous studies comparing adverse events between PROs versus clinician-reported outcomes (e.g., grading scales, diagnostic codes, or progress notes) in lung cancer [23], and mixed cancer types [24], patients generally reported symptoms earlier and more frequently than clinicians, had a higher incidence and severity of subjective toxicities, and had poor to modest agreement with clinician-reported values [23,24].…”
Section: Introductionmentioning
confidence: 99%